Planktonic foraminiferal Mg/Ca results from the eastern Fram Strait between 40 and 33.5 ka b2k - Wanyee Wong; Bjørg Risebrobakken; Malin Ödalen; Amandine Tisserand; Kirsten Fahl; Ruediger Stein; Eystein Jansen (PANGAEA, 2025)
We present a Neogloboquadrina pachyderma Mg/Ca-subsurface temperature (SubSTs) dataset from marine sediment core MD99-2304, retrieved from the eastern Fram Strait (77°37 extquotesingle15.6N, 9°56 extquotesingle54E) at a water depth of 1348 m. The core was collected using a piston corer during the Marion Dufresne IMAGES 5 expedition (leg MD114) in 1999. This dataset illustrates the subsurface condition in the eastern Fram Strait between 40 and 33.5 ka b2k, covering a period within Marine Isotope Stage 3 (MIS 3). Neogloboquadrina pachyderma specimens were dry-sieved between 150 and 212 μm and handpicked, with a temporal resolution of 20–40 years per sample. The final sampling resolution was determined by the availability of foraminifera in each sample. Trace element analysis was conducted on approximately 100 crushed foraminiferal shells per sample following a "full cleaning" protocol (Boyle, 1981; Boyle & Keigwin, 1985). This protocol involved the removal of clays, metal oxides, and barite, oxidation of organic matter, and surface leaching. Analyses were performed at the Trace Element Lab (TELab) at NORCE Bergen, Norway, using an Agilent 720 Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). Measured Mg/Ca ratios showed negligible correlation with Fe/Ca, Al/Ca, and Mn/Ca (r^2 = 0.003, 0.0067, and 0.002, respectively), confirming that contamination from incomplete cleaning was minimal. Long-term precision, assessed using the ECRM-752-1 carbonate standard, yielded a value of 3.76 mmol/mol (1σ = 0.007 mmol/mol). Mg/Ca(N.p) values were calibrated to SubSTs using the equation from Elderfield & Ganssen (2000): T = 10 exttimes ln(Mg/Ca(N.p) / 0.52).